Length-Weight Relationship of Three Indigenous Ornamental Fishes from North Eastern Hilly Region, Assam, India - Bijay Kali Mahapatra; Alakesh Pradhan; Shyam Kumar (Journal of Indian Fisheries Association, 2023)
Length-weight relationships of three indigenous ornamental fishes, namely: Pethia gelius (Hamilton, 1822), Oreichthys crenuchoides Schäfer, 2009 and Stigmatogobius sadanundio (Hamilton, 1822) were studied for the first time from the rivers and beels of North Eastern Hilly Region, Assam, India. A total of 362 fish specimens were collected for the present study on a monthly basis from August 2017 to April 2018 from landing center and local fishermen adjacent to Dihing River, Maguri beel, and Bogi beel. In the present study, b value from 2.016 to 2.588, showing allometric growth. The LWRs for three cyprinid species had not yet been reported for FishBase.